Increasing the indium incorporation efficiency during InGaN layer growth by suppressing the dissociation of NH3. (February 2017) - Yang, J.; Zhao, D.G.; Jiang, D.S.; Chen, P.; Zhu, J.J.; Liu, Z.S.; Liu, W.; Liang, F.; Li, X.; Liu, S.T.; Zhang, L.Q.; Yang, H.
Abstract: Three series of InGaN samples with different growth pressures are grown in a vertical metal organic chemical vapor deposition (MOCVD) system and the indium incorporation efficiency during InGaN layer growth is investigated. It is found that the indium content in InGaN layer decreases when the NH3 flow rate increases at a higher growth pressure and it increases with the NH3 flow rate at a lower growth pressure, This may be attributed to the higher dissociation rate of NH3 into N2 and H2 at a higher growth pressure, leading to a higher H2 concentration in reactor during InGaN growth. Therefore, changing growth conditions to suppress the dissociation of NH3 into N2 and H2 can increase the indium incorporation efficiency during InGaN film growth. Highlights: Apart from the protective effect of NH3 on InGaN growth, strong corrosive effect is observed when NH3 flow rate is too large. The dissociation of NH3 into H2 is the main reason for the decrease of indium content in InGaN when the NH3 flow rate is large. It is found that a low growth pressure is benefit for suppressing the dissociation of NH3 into H2 . Suppressing the dissociation of the NH3 during InGaN growth will increase the indium incorporation efficiency for InGaN layer.